Effect of aerobic exercise on balance in adults over 50 years: a meta-analysis of randomized controlled trials - Loría Calderón, Tyrone (2019)
The specific effect of aerobic exercise on balance is unclear. This meta-analysis examined the effect of aerobic exercise on balance in older adults. The systematic search was conducted on academic scientific bases: Academic Complete Search, ProQuest, PubMed, Science Direct and Sport Discuss, using the Boolean phrase: (aerobic exercise OR aerobic training) AND (adult* OR aging* OR senior* OR older adult*) AND (balance*) NO (diet or nutrition) NO (Animal) And random*. The inclusion criteria were publications in English or Spanish, full text, older adult (people and women), people over 50 years, experimental and quasi-experimental studies, treatment focused on aerobic exercise, and dynamic or static balance indistinctly of the type of test. We analyzed 4496 studies, and only 11 met the inclusion criteria, obtaining 56 effect sizes (TE) in 590 subjects. The moderator variables were age, sex, level of physical activity, health condition, N per study, duration of the session and exercise modality. The overall effect size for the experimental conditions was TE= 1.083, (p ≤ 0.05) (95% CI: 0.63 - 1.53, Q= 679.07, p= 0.00, I2= 99.55); the effect size of the control group was TE= 0.056, (p = 0.685) (95% CI: -0.14, .25, Q= 11.48, p=0.009, I2= 73.88). There were no differences in scores between the control groups of TE (n=16) and experimental group (n=40) (F= 2.73, p= .104). Aerobic exercise (AE) exerts a positive effect on the balance of older adults; therefore, AE training is a valid strategy to counteract the loss of balance in thisspecific group.